The Demographic Transition and Development in Africa The Unique Case of Ethiopia. - Teller, Charles; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2011)
Generalizations about the lack of demographic change and of progress in meeting the MDGs in sub-Saharan Africa are commonplace, but they are often misleading and belie the socio-cultural change. This book compares Ethiopia with other African countries, demonstrating the uniqueness of an African-type demographic transition: a mix of poverty-related negative factors with positive education, health and higher age-of-marriage trends that are pushing this population to accelerate the demographic transition and meet most of the MDGs. The book takes great care with challenges of inadequate data and weak analytical capacity to research this incipient transition, trying to unravel some complexities in Ethiopia: Slowly declining population growth rates with rapidly declining child mortality, very high chronic under-nutrition, low urban but high rural fertility; and high population-resource pressure along with rapidly growing small urban places.
Preface: Dr. Bill Butz, CEO -- Population Reference Bureau -- Forword: Charles Teller and Assefa Hailemariam -- Acknowledgements: Charles Teller and Assefa Hailemariam -- I. Introduction: Context & Framework -- 1. The Complex Nexus Between Population Dynamics and Development in sub-Saharan Africa: A New Conceptual Framework of Demographic Response and Human Adaptation to Societal and Environmental Hazards: Charles Teller and Assefa Hailemariam -- II. Demographic Transitions and Human Development -- 2. The Fertility Transition in sub-Saharan Africa -- 1990-2005: How Unique is Ethiopia?: Tesfayi Gebreselassie -- 3. The Nature -- Pace and Determinants of the Incipient Fertility Transition in Ethiopia -- 1984-2007: Can the 4.0 TFR target for 2015 be met?: Charles Teller -- Assefa Hailemariam and Tesfayi Gebreselassie -- 4. Demographic transition and the development Nexus: real dividend or burden?: Yordanos Seifu -- Solomon Ayalu and Mihiret Habte -- 5. Better Educated Youth as a Vanguard of Social Change? Adolescent transitions to later marriage and lower fertility in Southwest Ethiopia: Moshi O. Herman -- Dennis Hogan -- Tefera Belachew -- Fasil Tessema -- Abebe Gebremariam -- David Lindstrom -- III. Health and Nutrition -- 6.Women$1 (Bs Decision-making Autonomy and their Nutritional Status: A Socio-cultural Linking of Two MDGs: Yibeltal Tebekaw -- 7. Maternal Mortality and Human Development in Ethiopia: The Unacceptably Low Maternal Health Service Utilization and its Multiple Determinants: Munayie Seifu -- Mesganaw Fantahun -- Yirgu Gebrehiwot -- IV. Population Distribution -- Migration -- Urbanization and Labor Force -- 8. Migration and Urbanization: Addressing the Spatial Imbalance: Assefa Hailemariam and Aynalem Adugna -- 9. Rural-Urban Linkages in Ethiopia: Ensuring Rural Livelihoods and Development of Urban Centers; Aynalem Adugna and Assefa Hailemariam -- 10. The Importance of Permanent and Temporary Migration for Occupational Mobility in Urban Centers: Young Women are Doing Better than Young Men: Yambi Djamba & Charles Teller -- V. Vulnerability and Adaptation: Case Studies in Population-Resource Pressure and Food Insecurity -- 11. Urbanization and Changing Livelihoods: The Case of Farmers$1 (BDisplacement in the Expansion of Addis Ababa: Feyera Abdissa and Terefe Degefa -- 12. Malthusian or Bosrupian Consequences to Population Pressure and Food Insecurity? Vulnerability and Demographic Responses in 16 Drought-Prone Districts throughout Ethiopia: Charles H. Teller -- 13. Household Demographics -- Assets and Sustainable Rural Livelihoods: A Case Study from Rain-endowed South Western Ethiopia: Dula Etana -- VI. Development Policy and Program Evaluation -- 14. Population and Long-term Development Planning: Projecting an Unpredictable Future: Senait Tibebu -- 15. The National Population Policy (NPP) of Ethiopia: Achievements -- Challenges and Lessons learned -- 1993-2010: Assefa Hailemariam -- Solomon Alayu and Charles Teller -- 16.Barriers to Access and Effective Use of Demographic Data and Research for Development Policy in Ethiopia: Charles Teller -- Assefa Hailemariam and Negash Teklu -- VII. Conclusions and Policy Implications -- 17. Conclusions and Policy Implications: Charles Teller and Assefa Hailemariam -- Annexes: Index -- Author biographies.s
Keywords: Social sciences; Public health; Medical research; Population; Quality of life; Demography; Social Sciences; Demography; Population Economics; Public Health; Quality of Life Research; Electronic books